Segmental analysis of human hair reveals intra-annual variation in 25(OH)D3 concentrations in modern and archaeological individuals - Kate Britton; Orsolya Czére; Eléa Gutierrez; Linda M. Reynard; Eamon Laird; Gary Duncan; Baukje de Roos (Scientific Reports)
Abstract Vitamin D is essential for healthy skeletal growth and is increasingly recognised for its role in chronic disease development, inflammation and immunity. 25-hydroxyvitamin D3 (25(OH)D3) concentrations are an indicator of vitamin D status and are normally analysed in plasma or serum samples in clinical settings, while archaeological studies rely on the identification of skeletal markers of vitamin D deficiency, such as rickets. Here, we determined 25(OH)D3 concentrations in hair specimens (‘locks’) that had been sampled close to the root, aligned by cut end, and sliced into sequential segments from participants (n = 16), from Aberdeen, Scotland, using a modified protocol designed to minimise sample size. Concentrations were above detectable levels in 14 of 16 individuals, generating a (~ monthly) time-series of 25(OH)D3 concentrations, with fluctuating intra-hair trends consistent with the bioaccumulation of 25(OH)D3. In three participants, fluctuations in intra-hair 25(OH)D3 appear linked to recent significant weight loss, potentially due to the release of stored 25(OH)D3 from adipose tissue and subsequent uptake in hair. For the remaining participants, no statistically-significant correlations were determined between mean hair 25(OH)D3 levels and self-reported data, including age, sex, BMI, vitamin D supplementation, frequency of oily fish consumption, and hours spent outside. For a subset of our cohort (n = 4) isotope analysis highlighted potential relationships between elevated δ 18O values (which can indicate season of hair growth) and 25(OH)D3 concentrations in some individuals, which may reflect seasonally-increased UVB exposure. We also present data from an archaeological individual from the same city, with the addition of further isotope analysis (carbon, nitrogen, sulphur) to characterise diet. Results suggest possible positive correspondence of 25(OH)D3 levels with season in this archaeological individual, and possibly with marine protein consumption, highlighting the potential use of this approach in characterising the relationship between past vitamin D levels and diet. While results are promising, we recognise the limits of this study in terms of sample size and use of self-reported data, and further work is needed to better understand the relationship between serum and hair 25(OH)D3 before this approach can further be developed as either a non-invasive medical test or an archaeo-investigative technique.